Palynological and Stratigraphical Evidences on the Age of the Outcropped Khabour Formation near Chalki Nasara Village, Kurdistan Region, Northern Iraq - Baban, Dler H.; Lawa, Fadhil A. (Sulaimani Journal for Pure and Applied Sciences, 2016)
The siliciclastic predominate sequence of the Khabour Quartzite-Shale Formation crops out in Kurdistan Region within a narrow strip which runs semi-parallel to Iraq/Turkey border line, within the Imbricated and Thrusted Ora Zone, in front of the Bitlis Suture Zone which resulted from the collision of the Arabian and Anatolian plate. The studied samples from Chalki Nasara section appeared to be deposited within shallow marine environment and considered as a part of the Tectono- megasequence Ap.2. The identified seventy nine palynomorphs within the prepared palynological slides were all acritarchs with no observation of other known Lower Paleozoic palynomorphs like chitinozoa, scolecodonts, and graptolites. The identified acritarch species are among those which well documented in Cambrian and Ordovician periods such as Acanthodiacrodium angustum, Dactylofusa squama, Cristallinium cambriense, Saharidia fragilis, Acanthodiacrodium ubuii, Polygonium gracile, Acanthodiacrodium achrasii, Gonisphaeridium tener, Actinotodissus formosus, Polygonium pungens, Actinotodissus spinutisus, Cymatiogalea membranispina, Polygonium symbolum, Actinotodissus crassus. Accordingly and depending on the three distinguished acritarch assemblage palynozones and the stratigraphic position, the age of the lower unit of Khabour Formation in the studied area determined as Late Cambrian-Tremadocian. The dark brown and black colors of the identified palynomorphs within the formation indicated to thermally post mature condition of the organic matters. On the other hand, kerogen type I appeared to be the dominated quality of the existed organic matters and that based on the ratio between the different organic matter components.
Keywords: KurdistanKhabourPaleozoicAcritarchs